Agent‐based modeling may help to merge research traditions in foraging ecology in Europe and North America. (4th March 2017) - Guillemain, Matthieu; Elmberg, Johan; Pernollet, Claire A.; Arzel, Celine; Eadie, John M.
ABSTRACT: Although ducks have long been popular research subjects in both North America and Europe, geographical divergences in research orientation have developed during the past several decades for studying foraging ecology. In North America, foraging studies largely focused on the population level with an emphasis on foraging energetics aimed at improving waterfowl production through increased carrying capacity of wetlands in breeding areas, an approach later expanded to nonbreeding grounds. In Europe, studies have instead focused on inter‐individual differences in behavior of foraging ducks, with an emphasis on individual efficiency (e.g., methods, intake rate, patch choice) within the framework of optimal foraging theory. We suggest that agent‐based models (also termed individual‐based behavior models), which aim to predict habitat use from the heterogeneous behavior of different individual agents, can help to unify these approaches and would benefit considerably from increased collaboration and integration of the approaches of both North American and European researchers. © 2017 The Wildlife Society. Abstract : Duck foraging studies have largely focused on the population level with an emphasis on foraging energetics in North America, while Europeans have instead focused on inter‐individual differences in behavior of foraging ducks. Agent‐based models can help to unify these approaches and would improve waterfowl and wetland conservation in the 2 continents.